2003
DOI: 10.1097/01.sla.0000055271.58945.e2
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Pneumoperitoneum Modifies the Inflammatory Response to Sepsis

Abstract: Intra-abdominal CO2 present during laparoscopy attenuates the acute phase inflammatory response associated with perioperative sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 30 publications
5
47
1
3
Order By: Relevance
“…In the present study the total white cell count and circulating neutrophil were significantly lower following laparoscopic CLP using CO 2 than following LAP/CLP. Laparotomic CLP produced a significant reduction in lymphocyte count compared to laparoscopic CLP using CO2, corroborating with data from other authors 37 . Another work has shown a profound drop in white blood cells in animals subjected to laparotomy or pneumoperitoneum under intraperitoneal inoculation of Escherichia coli, without difference between them.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study the total white cell count and circulating neutrophil were significantly lower following laparoscopic CLP using CO 2 than following LAP/CLP. Laparotomic CLP produced a significant reduction in lymphocyte count compared to laparoscopic CLP using CO2, corroborating with data from other authors 37 . Another work has shown a profound drop in white blood cells in animals subjected to laparotomy or pneumoperitoneum under intraperitoneal inoculation of Escherichia coli, without difference between them.…”
Section: Discussionsupporting
confidence: 82%
“…This finding can be explained by the fact that pneumoperitoneum was performed with 3 mmHg pressure, sufficient to keep a normal and spontaneous respiration in rats. This pressure was used in rats by other investigators 37 . By the way, Kuntz et al 35 .…”
Section: Discussionmentioning
confidence: 99%
“…[6,10,14,35,36] In our study, in which these parameters were used, the total leukocyte count was observed to be significantly higher in the peritonitis-induced group than in the control group. However, the leukocyte count was significantly lower in the peritonitis and pneumoperitoneum-induced group in comparison with the sepsis group.…”
Section: Discussionmentioning
confidence: 87%
“…Another distinction between LRP and ORP is the use of CO 2 insufflation during LRP. Hanly et al 19 proposed that CO 2 -mediated attenuation of the acute phase response may be the underlying mechanism of reduced systemic inflammatory response reported in earlier laparoscopic surgeries. [20][21][22] The immune-modulatory effect of CO 2 is apparently mediated by peritoneal acidosis as acidic solutions had the same effect.…”
Section: Discussionmentioning
confidence: 99%